Физико-технологические основы получения резкого p–n-перехода - Karimov, A. V.; Yodgorova, D. M.; Yuldashev, Sh.Sh.; Boltaeva, Sh. Sh. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
A method for obtaining an abrupt p–n junction by liquid-phase epitaxy is presented. It consists in the growth of a thin intermediate p-type layer on a heavily doped p+ substrate, followed by the growth of an n-type layer from a melt cooled at a decreasing rate.